Challenges faced by employees in the financial sector: case of banking employees - BEN YACOUB, SARA (Revue du contrôle, de la comptabilité et de l’audit, 2025)
Employees in any sector and throughout their work process, face many difficulties and challenges. The financial sector is one of the most important sectors of an economy, as it plays an increasingly essential role in financing various infrastructures (roads, power plants, schools, hospitals, etc.). Employees in the financial sector may encounter challenges in their job due to the activity of the sector. In this article, we have tried to shed light on the different and main challenges encountered, the factors that lead to these challenges, and thus suggestions to minimize them. The results have shown us that the insufficiency of salaries and the demand of headquarters and customers are at the top of the challenges, thus the main factors are reflected in the progression of inflation and digitalization and thus the reduced number of employees which makes the number of tasks increased in relation to remuneration.